Wednesday

December 17, 2014

December 17, 2014

Posted by **Nipunika** on Wednesday, December 12, 2012 at 7:15am.

solve with steps

- Mathmatics -
**MathMate**, Wednesday, December 12, 2012 at 10:02amFirst simplify given expression

2a+6b-3(a+3b).... first remove parentheses

=2a+6b-3a-9b .... group like terms

=2a-3a +6b-9b .... sum like terms

=-a-3b

=-(a+3b)

Square expression

[-(a+3b)]^2 .... ^2 means raise to 2nd power

=(-1)^2 (a+3b)^2

=(a+3b)^2 .... use identity (x+y)^2=x^2+2xy+y^2

=a^2+6b+9b^2

**Answer this Question**

**Related Questions**

AP Physics - A Young's double slit has a slit separation of 2.50x10 raised to ...

testing of materials - How do I solve these two problems ? 1.The mass of a ...

math - 5x^-1/-y^-1 once again, what are you asking? how is this simplified -y/5x...

Algebra 2 URGENT - Simplify: 4s raised to the negative 2 power - (4t)raised to ...

Algebra - how to tell the difference between a negative number raised to a power...

ALGEBRA 1 - ok the question is Describe how you would help a friend who needs to...

Math - Find how much money there will be in the account after the given number ...

Algebra 2 - I know that were doing problems were there is a soultion given which...

Math - Find the values of x when, x raised to the power root x = x raised to the...

Math - Find the values of x when, x raised to the power root x = x raised to the...